Aspectos historicos en el conocimiento cientifico de los pueblos indigenas pampeano-patagonicos. - Priegue, Celia Nancy (Departamento de Humanidades, Universidad Nacional del Sur, 1992)
"A study of the indigenous peoples of Patagonia and Pampa, based on both primary and secondary sources. Uses linguistic and ethnographic observations to review and reassess earlier reports and interpretations" -- Handbook of Latin American Studies, v. 58.